Years of life lost: A call to achieve equitable end-of-life care among children - Aysha Jawed (Health Promotion Perspectives, 2022)
Significant disparities continue to exist in access to inpatient pediatric hospice care among children at the end-of-life. Increasingly more children at this stage are dying in the hospital or at home on hospice which is not always an acceptable option to the children and their families. Two clinical case examples illustrate implementation of these options in practice. A missing link exists in healthcare systems across developed and developing countries in pediatric end-of-life care. Currently, the primary options involve selecting between hospital and home-based hospice care. Proposing to increase access to inpatient pediatric hospice services could potentially increase acceptability of this option to honor the child in line with the family’s preferences, goals, wishes, and values. In addition, inpatient pediatric hospice could offset costs from preventable hospitalizations and overall high-cost healthcare utilization. Oftentimes, readmissions impact decision-making among caregivers that include changes in code status from Do Not Resuscitate/Do Not Intubate (DNR/DNI) to full curative care, thereby resulting in medicalization or overmedicalization of the child. It follows that reduced healthcare expenditures will increase cost efficiency across the healthcare system. Achieving health equity in palliative care among adult and pediatric patients at the end-of-life is a longstanding goal of the World Health Organization (WHO) and the United Nations International Children’s Emergency Fund (UNICEF). Proposing to mitigate disparities in palliative care among children through inpatient hospice as another viable option for their families could contribute to the larger overarching goal of achieving health equity in end-of-life care across the world.